Modulatory Activity of Soluble Beta Amyloid on HPA Axis Function in Rats - Grazia Morgese, Maria; Tucci, Paolo; Colaianna, Marilena; Zotti, Margherita; Cuomo, Vincenzo; Schiavone, Stefania; Trabace, Luigia (Current Pharmaceutical Design, 2014)
Despite the consolidation of the amyloid hypothesis, the main component of senile plaques in Alzheimer’s disease (AD), recent findings have led to a conceptual shift opening new questions about the potential physiological role of this peptide. In addition, soluble beta amyloid (sBA), in transgenic AD model, resulted to be increased after chronic and acute stress and alterations in cortisol levels have been reported in AD. Impaired hypothalamic pituitary adrenal (HPA) axis has been linked to depressive state and, consistently, we have previously demonstrated that BA is able to provoke depressive-like profile in rats. Here we further analysed the effect of the peptide in behavioural paradigms used to study emotional and cognitive response, by using the passive avoidance task, for cognitive parameters, and the sucrose preference test (SPT), to evaluate anhedonia. Moreover, in order to correlate behavioural with neurochemical and neuroendocrinal data, we investigated the effects of the peptide on noradrenergic system in amygdala (AMY), prefrontal cortex (PFC) and hippocampus (HIPP) along with plasmatic corticosterone and hypothalamic corticotrophin releasing factor (CRF). We found that BAtreated animals showed an impaired memory consolidation of inhibitory avoidance training, while no effect was evident in SPT. These results lead us to hypothesize a different response to stress coping behaviour in BA treated rats. Moreover, BA caused a significant increase in noradrenaline (NA) in PFC and HIPP, while in AMY was decreased. Consistently, we found a significant decrease in plasma corticosterone concentrations in BA-treated rats. Taken together, our data suggest that BA exerts an inhibitory effect on HPA axis activation.
Keywords: HPA